ACE gene in pregnancy complications: Insights into future vascular risk. (2nd January 2016) - Fatini, Cinzia; Romagnuolo, Ilaria; Sticchi, Elena; Rossi, Lorenza; Cellai, Anna Paola; Rogolino, Angela; Abbate, Rosanna
ABSTRACT: Objective : A history of placenta-mediated pregnancy complications (PMPCs) increases the risk of cardiovascular disease later in life, possibly related to the persistence of endothelial dysfunction. We performed this study in order to search for a common genetic background shared by women with a history of PMPC and vascular disorders, due to their common pathophysiologic pathway of endothelial dysfunction. Methods : We analyzed the prevalence of seven polymorphisms in ACE, AGTR1, AGT, and eNOS genes, endothelial-function related, in 290 women with a history of premature cardiovascular events (CVDs), and in 367 women with a history of PMPC (preeclampsia (PE), stillbirth (SB), and small for gestational age (SGA)), compared with 300 healthy women (HW) who delivered after uneventful pregnancy (HW). Results : ACE D allele frequency was similar between women with history of CVD and PMPC, and significantly higher than that observed in HW [OR (95% CI) 1.91, p = 0.002, and OR (95% CI) 2.18, p < 0.0001, respectively]. In women carrying ACE-240T or eNOS-786C allele, a two-fold increase in SB susceptibility was evidenced ( p = 0.004 and p = 0.005, respectively). Women with a history of SB and premature CVD exhibited a significantly higher unfavorable allelic burden ≥ 3 in comparison to that observed in HW ( p < 0.0001 and p = 0.002, respectively). Conclusions : Our findings demonstrate a common genetic background shared by women with a history of vascular disorders and PMPCs; pregnancy may be considered a window to future cardiovascular risk; therefore, "non-classic" genetic biomarkers of endothelial dysfunction might allow one to identify women who could have a greater benefit for an early cardiovascular screening and prevention.